Variation of Photosynthetic Induction in Major Horticultural Crops Is Mostly Driven by Differences in Stomatal Traits - Zhang, Ningyi; Berman, Sarah R.; Joubert, Dominique; Vialet-Chabrand, Silvere; Marcelis, Leo F. M.; Kaiser, Elias (Frontiers in Plant Science, 2022)
Under natural conditions, irradiance frequently fluctuates, causing net photosynthesis rate (A) to respond slowly, and reducing yields. We quantified genotypic variation of photosynthetic induction in 19 genotypes among six horticultural crops: basil, chrysanthemum, cucumber, lettuce, tomato and rose. Kinetics of photosynthetic induction and stomatal opening were measured by exposing shade-adapted leaves (50 mol m-2 s-1) to a high irradiance (1000 mol m-2 s-1), until A reached a steady state. Rubisco activation rate was estimated by kinetics of carboxylation capacity, which were quantified using dynamic A versus [CO2] curves. Generally, variations in photosynthetic induction kinetics were larger between crops, and smaller between cultivars of the same crop. Time until reaching 20-90% of full A induction varied by 40-60% across genotypes, and this was driven by variation in stomatal opening rather than Rubisco activation kinetics. Stomatal conductance kinetics were partly determined by differences in stomatal size and density; species with densely packed, smaller stomata (e.g. cucumber) tended to open their stomata faster, adapting stomatal conductance more rapidly and efficiently than species with larger but fewer stomata (e.g. chrysanthemum). We conclude that manipulating stomatal traits may speed up photosynthetic induction and growth of horticultural crops under natural irradiance fluctuations.